The critical thinking tool kit : spark your team's creativity with 35 problem solving activities - Caroselli, Marlene (AMACOM, 2011)
ItÆs not just for geniuses. Everyone can learn to think creatively, analytically, and quickly with brain-boosting activities for the workplace. Unimaginative. Risk-adverse. Prone to group-think. These are not just empty complaints about todayÆs employees. A recent article in Newsweek found solid data that proves a ôcreativity crisisö is plaguing America. Yet critical thinking, the ability to approach a problem both analytically and creatively, is the bedrock of success for companies and their people. Fortunately, itÆs a skill that can be learned. The Critical Thinking Tool Kit aims to get empl.